2021
DOI: 10.3389/fonc.2021.665037
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Soluble Mediator Signatures of Patients With Philadelphia Chromosome-Negative Myeloproliferative Neoplasms

Abstract: BackgroundEssential thrombocythemia (ET), polycythemia vera (PV), and primary myelofibrosis (PMF) are clonal hematological diseases classified as Philadelphia chromosome-negative myeloproliferative neoplasms (MPN). MPN pathogenesis is associated with the presence of somatic driver mutations, bone marrow (BM) niche alterations, and tumor inflammatory status. The relevance of soluble mediators in the pathogenesis of MPN led us to analyze the levels of cytokines, chemokines, and growth factors related to inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…CSF1 can promote differentiation of HSPCs towards the myeloid lineage 65 and CSF2 has been shown to be required for differentiation of precursor cells towards the myeloid/erythroid fate 66 . We also observed increased accessibility of the CCL2 gene, a key cytokine mediating monocyte recruitment to inflammatory sites 67 , which has been reported to be increased in MF 68 .…”
Section: Resultssupporting
confidence: 66%
“…CSF1 can promote differentiation of HSPCs towards the myeloid lineage 65 and CSF2 has been shown to be required for differentiation of precursor cells towards the myeloid/erythroid fate 66 . We also observed increased accessibility of the CCL2 gene, a key cytokine mediating monocyte recruitment to inflammatory sites 67 , which has been reported to be increased in MF 68 .…”
Section: Resultssupporting
confidence: 66%
“…5A), a markers of fibroblast activation(53). A significant increase in soluble IL11 was also observed (54)(Fig. 5B).…”
Section: Resultsmentioning
confidence: 69%
“…The pro-in ammatory status seem to contribute to MPN pathophysiology [4,6,8], once the isolated presence of driver mutations are insu cient to fully explain the mechanisms underlying the MPN pathogenesis, progression and phenotypes [27]. Many authors have reported the association of oncoin ammation [6, 7, 8, 27] with genetic instability, symptomatology, endothelial dysfunction and procoagulant state in MPN [9,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the genetic alterations, MPN are considered as oncoin ammatory diseases due to exacerbated in ammatory status [6,7,8]. Recent studies have reported increased levels of pro-in ammatory cytokines, chemokines and growth factors in bone marrow niche and peripheral blood from PV, ET and MF patients [6, 9, 10] and associated them with patients' clinic-laboratory parameters [9,10]. Therefore, the proin ammatory pro le seems to contribute genetic and epigenetic instability, predisposition to cardiovascular events, brotic progression and leukemic transformation in MPN [5,6,11,12].…”
Section: Introductionmentioning
confidence: 99%